Chartergellus jeannei, a New Species of the Swarming Social Wasps from the Amazon Forest ( Hymenoptera: Vespidae: Epiponini) - Grandinete, Y. C. (2015)
A new species, Chartergellus jeannei Andena &Soleman, is described.